British society is heading for levelling down - Dorling, DFL (LSE Politics and Policy Blog, 2023)
In his new book “Shattered Nation: Inequality and the Geography of a Failing State”, Danny Dorling paints a bleak picture of life for many UK citizens today. Standards of living are falling across the country, yet policy-makers from across the political spectrum have failed to put forward effective measures to reverse this decline. In this Q&A with Bea White, he explains why radical change may be inevitable for a country that has run out of both money and options.